2015
DOI: 10.1111/asj.12418
|View full text |Cite
|
Sign up to set email alerts
|

Secretory pattern and regulatory mechanism of growth hormone in cattle

Abstract: The ultradian rhythm of growth hormone (GH) secretion has been known in several animal species for years and has recently been observed in cattle. Although the physiological significance of the rhythm is not yet fully understood, it appears essential for normal growth. In this review, previous studies concerning the GH secretory pattern in cattle, including its ultradian rhythm, are introduced and the regulatory mechanism is discussed on the basis of recent findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Concentrations of hormones and growth factors also vary in serum and mammary secretions during the perinatal period. Growth hormone is released from the anterior pituitary in a pulsatile manner similar to other species (Tannenbaum and Martin, 1976;Plouzek and Trenkle, 1991;Kasuya, 2015). The episodic release of GH for lactating cows was first reported by (Vasilatos and Wangsness, 1981) who observed 8 to 9 GH spikes per day.…”
Section: Content Of Selected Bioactive Substances In Bovine Blood and Mammary Secretionsmentioning
confidence: 92%
“…Concentrations of hormones and growth factors also vary in serum and mammary secretions during the perinatal period. Growth hormone is released from the anterior pituitary in a pulsatile manner similar to other species (Tannenbaum and Martin, 1976;Plouzek and Trenkle, 1991;Kasuya, 2015). The episodic release of GH for lactating cows was first reported by (Vasilatos and Wangsness, 1981) who observed 8 to 9 GH spikes per day.…”
Section: Content Of Selected Bioactive Substances In Bovine Blood and Mammary Secretionsmentioning
confidence: 92%
“…Produced by the anterior pituitary gland, bovine somatotropin is a protein hormone that stimulates growth and affects a variety of metabolic processes. In addition to increasing the lipolytic activity of adipose tissue and inhibiting the transmission activity of glucose into tissue, it directly or indirectly stimulates growth processes, such as cell division, bone growth, and protein synthesis [ 20 ]. In recent years [ 21 ], somatotropin (ST) has been found to significantly affect lactation in ruminant animals, and the concentration of pituitary hormone is also directly related to lactation in cows.…”
Section: Hormonal Regulation Of Lactation In Dairy Cowsmentioning
confidence: 99%
“…Because it has been reported that GH is secreted in pulses with a frequency of approximately 6 h in sheep, cattle, and deer, and that there is a secretory burst around the anticipated time of meal supply but no other secretion for about an hour after feeding (McMahon et al, 2001), the samples were taken just before the morning meal to limit the effects of pulsatility, at the same time and day in both species. Indeed, Kasuya (2016), in a review dedicated to the secretory pattern of GH in cattle, highlighted that in full-fed cattle, there is high synchronicity of the pattern based on the distance from the meal.…”
Section: Growth Hormonementioning
confidence: 99%